The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3168/jds.2020-19533
|View full text |Cite
|
Sign up to set email alerts
|

Breeding goal traits accounting for feed intake capacity and roughage or concentrate intake separately

Abstract: Current breeding tools aiming to improve feed efficiency use definitions based on total dry matter intake (DMI); for example, residual feed intake or feed saved. This research aimed to define alternative traits using existing data that differentiate between feed intake capacity and roughage or concentrate intake, and to investigate the phenotypic and genetic relationships among these traits. The data set contained 39,017 weekly milk yield, live weight, and DMI records of 3,164 cows. The 4 defined traits were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Data from 329 French Holstein cows were collected from 2014-2020, at the Le Pin and Méjusseaume research herds (Martin et al, 2021a;Lefebvre et al submitted to WCGALP 2022). Data from 1,953 Dutch Holstein cows were collected from 1991-2019, in different research herds at Wageningen University (Heida et al, 2021). The Danish, French and Dutch data were shared as a part of the Gentore project (https://www.gentore.eu).…”
Section: Methodsmentioning
confidence: 99%
“…Data from 329 French Holstein cows were collected from 2014-2020, at the Le Pin and Méjusseaume research herds (Martin et al, 2021a;Lefebvre et al submitted to WCGALP 2022). Data from 1,953 Dutch Holstein cows were collected from 1991-2019, in different research herds at Wageningen University (Heida et al, 2021). The Danish, French and Dutch data were shared as a part of the Gentore project (https://www.gentore.eu).…”
Section: Methodsmentioning
confidence: 99%
“…Residual feed intake (RFI) is a moderately heritable trait that expresses the difference between actual feed consumed and predicted feed intake based on maintenance and growth; the lower the RFI value the more efficient the animal is ( Heida et al., 2021 ; Johnson et al., 2019 ; ( Terry et al., 2021 ). Wang et al.…”
Section: Maternal Nutrition Foetal Development and Bullsmentioning
confidence: 99%
“…Feed conversion ratio (FCR) expresses the amount of feed required to produce 1 kg of liveweight ( Heida et al., 2021 ; ( Terry et al., 2021 )). A feedlot study by ( Fox, Tedeschi and Guiroy, 2001 ) found that a 10% FCR increase results in a 43% increase in profit, whilst a 10% ADG increase resulted in an 18% profit increase.…”
Section: Backgroundingmentioning
confidence: 99%